Bio-based elastomer nanoparticles with controllable biodegradability. Issue 104 (26th October 2016) - Wang, Qingguo; Zai, Yingying; Yang, Dejing; Qiu, Liyan; Niu, Chengqun
Abstract : Using melt polycondensation of bio-derived dicarboxylic acids and diols, followed by polyester emulsification and radiation, we fabricate the bio-based elastomer nanoparticles with controllable biodegradability, which can be used in biomedical fields. Abstract : Recently, biodegradable polymers and nanoscale polymers have become hot topics in advanced polymer research. In this manuscript, we report novel electron beam irradiation vulcanized soft polyester nanoparticles through a three-step method. Some dicarboxylic acids ( e.g., succinic acid, sebacic acid, itaconic acid) and diols ( e.g., 1, 3-propanediol and 1, 4-butanediol), which can also be derived from biomass resources, were firstly synthesized into the aliphatic unsaturated polyester by using melt polycondensation, which was followed with polyester emulsification and radiation crosslinking to obtain the elastic polyester nanoparticles. Interestingly, the crosslinked soft polyester nanoparticles with controllable gel content, controllable biodegradability (exhibiting a weight loss ratio of 52.3% within 5 days in the presence of lipase) and low glass transition temperature of about −55 °C are potential candidates to meet the requirements not only for drug delivery carriers but also for modifying some biodegradable brittle polymers which are widely used in pharmaceutical sciences, biotechnology, and biomedicine.